Effective biosorption of methylene blue dye from aqueous solution using wild macrofungus (Lactarius piperatus) - Isik, Birol; Ugraskan, Volkan; Cankurtaran, Ozlem (Separation science and technology, 2022)
In this study, the biosorption of methylene blue (MB) dye using the wild macrofungus (Lactarius piperatus) (LP) was studied. To determine the optimum conditions, the effects of contact time, initial pH (2-12), and biosorbent dosage (1-5 g/L) on the biosorption at different temperatures (25-55°C) and dye concentrations (10-50 mg/L) were investigated. The studies showed that the biosorption percentage of 86.5 ± 0.5% was reached at 25°C and pH = 7. From the Langmuir isotherm, the maximum adsorption capacity was found as 384.6 ± 3.4 mg/g in pH = 7 and 833.3 ± 4.9 mg/g in pH = 12 at 25°C, respectively. Furthermore, it was obtained that the biosorption takes place physically according to the energy value calculated using the D-R model. As a result of the kinetic studies, it was determined that the biosorption followed the pseudo-second-order model. According to the thermodynamic parameters, it can be said that the biosorption is exothermic and spontaneous. Besides, error analyses were carried out to evaluate the repeatability and accuracy of the results. The obtained results reveal that LP could be an efficient biosorbent to remove dyes from the aqueous solution.